Lobi dan Negosiasi Dalam Komunikasi Antara Pihak Klien Dengan PT Digirmarly - Alifya Dyara Sruti; Agnie Bulan Rachmadhany; Tabina Ratnadewati; Saifuddin Zuhri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to understand the communication carried out by PT Digimarly Solusi Digital in carrying out the lobbying and negotiation process with clients so as to create mutually beneficial cooperation. The theory applied in this research is Persuasion Communication Theory because this theory is related to the lobbying and negotiation process where individuals or groups involved in the lobbying and negotiation process must have the ability to convince interested parties to agree and adopt a certain attitude, statement, opinion, and behavior. The methodology used is qualitative research, with the research subject being PT Digimarly Solusi Digital which is a social media service company that provides digital marketing consulting services to the community, especially MSME players. Data was collected through in-depth observations and interviews with the Head of Department of Sales and CRM (Customer Relationship Management) as well as through library research. The results showed that the lobbying and negotiation strategies applied were Direct Lobbying and Win-Win Solution with the Cognitive Problem and Networking approach methods which aimed to equalize perceptions between PT Digimarly Solusi Digital and clients so as to find a mutually beneficial cooperation agreement between the two parties and maintain a long-standing good relationship.